Gender, Sexuality and the UN's SDGs: a multidisciplinary approach - Dalton, Drew; Smith, Angela (Sustainable development goal series, 2023)
Against the backdrop of Covid-19, this edited volume will utilize a gendered lens to explore the United Nation's Sustainable Development Goals (SDGs), with a clear focus on challenging the omission of sexuality in relation to the SDGs as well as analyzing the ways in which the SDGs are also equally relevant for Western countries. While acknowledging the importance of these goals, contributors unpack the exclusion of marginalized genders and sexualities as well as how popular media and social media contribute to the wider understanding of issues of gender and sexuality and the SDGs. This volume also dispels assumptions about the irrelevance of SDGs to countries in the West, with a particular focus on the UK. Chapters examine a variety of topics including: HIV/AIDS, sex work, global migration, climate change and environmental sustainability, poverty, education, and sexual harassment. This collection will be of interest to scholars, researchers, and students across Sociology, Gender & Sexuality Studies, Education, Development Studies and Sustainability Studies.